A decade in focus: occupational health and safety research trends - a bibliometric approach - Dipak Mahat; Dasarath Neupane; Sajeeb Kumar Shrestha (International Journal of Occupational Safety and Health, 2025)
Introduction: Occupational health and safety (OHS) is a critical area of research due to its direct impact on worker well-being and productivity. Understanding the evolving trends and patterns within this domain provides valuable perspectives on the global focus and advancements made over the past decade. This study conducts a bibliometric analysis of OHS literature to map its intellectual structure, identify influential contributors, and highlight emerging themes.